Examining the Impact of Career Coaching Practices on Career Decision Self-Efficacy and Career Stress Levels of University Students: The Case of Izmir Katip Çelebi University - Esen, Murat; İpçi, Taylan (International Journal of Contemporary Economics and Administrative Sciences, 2022)
The choices made by university students in the process of making career decisions are one of the most important decisions they make in their lives. The aim of this study is to examine the impact of career coaching practices on the career decision self-efficacy and career stress levels of university students. The sample of the study is of senior students studying in the Department of Business Administration of Izmir Katip Çelebi University in the 2018-2019 academic year. A total of 24 people were taken to the study, including 12 (6 females and 6 males) in the study group and 12 (6 females and 6 males) in the control group. Sociodemographic form, Career Decision Self-Efficacy Scale (CDSES) and Career Stress Scale (CSC) were used as data collection tools. The students in the experimental group were given a 6-week career coaching program developed by the researcher, each for 60 minutes. Levene’s test, t-test and ancova were used in statistical data analysis. As a result of the study, it was determined that the practice of career coaching increases the career decision self-efficacy of the students in the working group and reduces their level of career stress.